PRAKTIK SEWA SAWAH SISTEM BAYAR PANEN (YARNEN) PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Hendi Suardana; Irvan Iswandi (Melati Institute, 2022)
Gantar Village in Indramayu Regency is a village which becomes national rice barn. Most of villagers are farmers from time to time, but not all of them have rice field or area as the place for farming. Most of Gantar Village people who do not have rice field usually rent it from the neighbors as the farming facility or usually called as Ijarah. Through the writing of this undergraduate thesis, the researcher would like to find out if the practice of Rice Field Rent Harvest Payment System (Yarnen) at Blok Nambo Gantar Village, Gantar Sub District, Indramayu Regency is already in accordance with the Positive Law and Islamic Law or not. In this undergraduate thesis, the researcher employed qualitative approach method which aimed to understand the social situation, events, roles, interaction and groups, and it gives recent information until it is beneficial for the development of science and to be applied in various fields. The results of this research showed that the implementation of rice field rent harvest payment system at Blok Nambo Gantar Village Gantar Sub District Indramayu Regency is rent agreement which has been conducted hereditarily. The agreement was conducted between two parties; the first party was the rice field owner and the second party was the rice field tenant. According to the positive law, the practice of rice field rent is legitimate according to Code of Civil Law Article 1548 which mentions that an agreement where one party ties himself/herself up to give the pleasure of certain goods to another party for certain period of time. According to the Islamic Law, the practice of rice field rent at Blok Nambo has fulfilled the principles and requirements of Islamic Law.